The international law of the sea - Tanaka, Yoshifumi (Cambridge University Press, 2015)
This new edition has been fully revised and updated to include the contemporary issues together with new cases delivered by international courts and tribunals, such as the ICJ, ITLOS and Arbitral Tribunals, treaties, UN resolutions, and other instruments. It retains the clear chapter structure of the first edition, but has expanded the topics on marine spaces beyond national jurisdiction, maritime delimitation, protection of the marine environment.